Surviving the Applewhites - Tolan, Stephanie S. (Scholastic, 2002)
Jake, a budding juvenile delinquent, is sent for home schooling to the arty and eccentric Applewhite family's Creative Academy, where he discovers talents and interests he never knew he had.